Transposase-mediated gene modulation in the placenta. (November 2017) - Elston, Marlee; Urschitz, Johann
Abstract: The placenta is an organ vital to fetal development as well as the maintenance of a healthy pregnancy and plays a crucial role in developmental programming of the fetus. The mechanisms that link intrauterine milieu, fetal health and disease development later in life are poorly understood. Placenta-specific gene modulation, both by generating transgenic animals as well as by developing methods for in vivo genetic modifications is a growing area of interest as this approach provides the opportunity to investigate the role of particular genes or gene networks in regulating placental function and fetal growth. Furthermore, in vivo placental gene transfer may be adapted to treat humans in the future and could be used as an early intervention strategy for a wide range of pregnancy complications. This review is an overview of transposase-based methods available for both transgenic animal generation and in vivo placental gene modifications with an emphasis on piggyBac-based systems.